Chronic cerebral blood flow alterations in traumatic brain injury and sports-related concussions. (3rd July 2022) - Vedung, Fredrik; Fahlström, Markus; Wall, Anders; Antoni, Gunnar; Lubberink, Mark; Johansson, Jakob; Tegner, Yelverton; Stenson, Staffan; Haller, Sven; Weis, Jan; Larsson, Elna-Marie; Marklund, Niklas
ABSTRACT: Primary Objective: Traumatic brain injury (TBI) and sports-related concussion (SRC) may result in chronic functional and neuroanatomical changes. We tested the hypothesis that neuroimaging findings (cerebral blood flow (CBF), cortical thickness, and 1 H-magnetic resonance (MR) spectroscopy (MRS)) were associated to cognitive function, TBI severity, and sex. Research Design: Eleven controls, 12 athletes symptomatic following ≥3SRCs and 6 patients with moderate-severe TBI underwent MR scanning for evaluation of cortical thickness, brain metabolites (MRS), and CBF using pseudo-continuous arterial spin labeling (ASL). Cognitive screening was performed using the RBANS cognitive test battery. Main Outcomes and Results: RBANS-index was impaired in both injury groups and correlated with the injury severity, although not with any neuroimaging parameter. Cortical thickness correlated with injury severity (p = 0.02), while neuronal density, using the MRS marker ((NAA+NAAG)/Cr, did not. On multivariate analysis, injury severity (p = 0.0003) and sex (p = 0.002) were associated with CBF. Patients with TBI had decreased gray (p = 0.02) and white matter (p = 0.02) CBF compared to controls. CBF was significantly lower in total gray, white matter and in 16 of the 20 gray matter brain regions in female but not male athletes when compared to female and male controls, respectively. Conclusions: Injury severity correlated with CBF, cognitive function, and cortical thickness. CBF also correlated with sex and was reduced in female, not male, athletes. Chronic CBF changes may contribute to the persistent injury mechanisms in TBI and rSRC.